Supervisi Kurikulum dalam Era Digital: Menghadapi Tantangan dan Peluang - Nani Septiana; Puput Anggraini; Ahmad Khotib; Ainur Rofiq (Jurnal Budi Pekerti Agama Islam, 2025)
Technological developments can increase the effectiveness of curriculum supervision, however the challenges of unequal access and lack of training must still be overcome to achieve optimal learning goals. The aim of this research is that researchers state Curriculum Supervision in the Digital Era in Facing Challenges and Opportunities that digital-based supervision can increase efficiency, make monitoring easier, and provide faster feedback to educators and students. This research design uses a qualitative type with a case study approach to understand in depth the implementation of curriculum supervision in the digital era at SMA Darussalam Blokagung. Sources of informants in this research include: Principals, teachers and students of Darussalam High School. The data collection technique in this research is observation. Interviews and documentation. Data analysis in this research uses the Miles Huberman model with 3 stages including data reduction, data presentation and drawing conclusions. The results of this research: Curriculum Supervision in the Digital Era in Facing Challenges and Opportunities produced findings including: varied learning styles, Teacher training and innovative curriculum.